Respostas

A melhor resposta!
2014-04-21T16:06:57-03:00
Pela Fórmula:
 a_n = a_1 + (n-1).r

Vamos usar o que ele nos Dá:


I-)  \left \{ {{a_2 = a_1 + (2-1) . r} \atop {a_3 = a_1 + (3-1) . r}} \right.  SOMANDO

a_2+a_3 = 2a_1 +3r   como a_2 + a_3 = 11 Temos :

2a_1 + 3r = 11

II-)   \left \{ {{a_4 = a_1 + (4-1) . r} \atop {a_7 = a_1 + (7-1) . r}} \right.
SOMANDO

a_4+a_7 = 2a_1 +9r  como a_4 + a_7 = 21 Temos:

2a_1 + 9r = 21

ULTIMO SISTEMA :

 \left \{ {{2 a_1 +3r = 11} \atop {2a_1 + 9r = 21}} \right.

Resolvendo: a Razão  = 
 \frac{5}{3}

1 5 1